Notes on the breeding behaviour of captive Whistling Swans - Evans, Mary E (Wildfowl, 1977)
The incubation behaviour of a pair of captive breeding Whistling Swans Cygnus c. columbianus was studied. The male shared in nest building and sat on the eggs while the female was off feeding.